Pembelajaran Al-Qur'an dengan Rasm Madinah dan Rasm Indonesia Pada Anak Usia Sekolah Dasar/ Mdrasah Ibtidaiyah - Mauizdati, Nida (Journal of Islamic Education, 2025)
The researcher does this research because the rasm circulating in indonesia quite varied. There are rasm madani and rasm indunisi. Every mushaf has different rasm characteristics. On the other hand, learning to read the Qur'an is a very important thing for children from an early age. This study aims to know learning to read Al-Qur'an with rasm madani and rasm indunisi for elementary school students. This study refers to how the systematic learning materials and the methods of learning are applied. This research is a library research in the field of learning Al-Qur'an. The researcher examines the textbook of learning the Qur'an. Therefore, to obtain the necessary data, the researcher conducted a library survey to inventory the literature related to this research. The results of this study indicate that the rasm madani and rasm indunisi have some differences. In terms of punctuation, the rasm madani is more complicated than the rasm indunisi. Even so, in the rasm madani, the rules of recitation of the Qur'an are already visible through its Quranic punctuation. In contrast to the rasm madani, rasm indunisi is more simpler. However, the learning of rasm indunisi requires the habituation and emphasis on learning correct pronunciation, tajwid. The learning of Qur'an can be applied with the individual and classical approach and reading-listening technique and alphabet method, sound method, imitative method, and integrated method.